Panic Disorder with Agoraphobia in Post-Trauma Epilepsy Patient: a Case Report - Fitriani, Fatimah; Ami Putra, Gumilar Fardhani; Syulthoni, Zain Budi (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2024)
Epilepsy is a significant health problem in society. Epilepsy prominently affects a person's quality of life, including social and psychological aspects, with the community’s negative attitude and stigmatization also contributing to the decline of quality of life. Psychiatric comorbidities such as anxiety and mood disorders are found to be the most common comorbidities in epilepsy. We reported a 31-year-old male with anxiety, palpitations, headache, and nausea. These complaints were often felt by the patient in a crowded place and his wife did not accompany him. These complaints have been felt by the patient since his father died in 2014. He also had a history of seizures after an accident in 2008, although the seizures had been decreased to 3 to 4 times a month. The patient always worried that the seizure would recur. Examinations showed severe anxiety and moderate depression. EEG showed functional disturbances with epileptogenic potential. CT scan showed gliosis and temporal bone defect. The patient was diagnosed with post-trauma epilepsy and agoraphobia. The patient was treated with antiseizure, sleeping pills, antidepressants, cognitive behavioral therapy, psychotherapy, relaxation therapy, and family psychoeducation. 1 week after treatment, the headache was significantly reduced, and the patient reported sleeping better. This report showed the importance of assessing and treating psychiatric comorbidities in patients with epilepsy to improve their quality of life.